Peningkatan Pelayanan Terhadap Masyarakat Melalui Pelatihan Empati dan Dasar Konseling pada Staf BAPAS Klas I Bandung - Astri Firdasannah; Rina Ruth Polla (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
Teenage prisoners who have passed 2/3 of their sentence participate in a parole period, where they are returned to their families and become clients of BAPAS. During the parole period, teenagers are obligated to report to their Probation Officers (PO). With the assistance of POs, it is hoped that these teenagers can maintain stability in their lives and refrain from repeating their offenses. POs have the responsibility to provide guidance to parole clients undergoing reintegration programs. However, executing this task is not easy. Therefore, a basic counseling training program for POs is highly necessary. This is realized through an in-house training program aimed at enhancing service to the community through empathy and basic counseling training. The training program on empathy and basic counseling proves effective in improving participants' knowledge about empathy and basic counseling, as evidenced by the increase in post-test scores regarding participants' knowledge of empathy and basic counseling.